Attitudes on peer evaluation of teaching among academic staff of the Faculty of Medicine, University of Colombo - Wasalathanthri, S.; Atapattu, P.A.; Nanayakkara, U.; Jayasekara, R.J.W. (My University, 2012)
Teaching is a multidimensional task which needs continuous evaluation. Peer evaluation is considered superior to student feedback because peer critique usually encompasses expert subject knowledge and teaching-learning strategies. Though peer evaluation may be subjective, this can be minimized by using a pre-formed protocol for observation. Peer review of teaching promotes continuing professional development of individual teachers and is an integral part of quality assurance. Attitudes of academic staff regarding peer evaluation may contribute significantly to the success of the implementation and optimal outcomes of peer evaluation.